Turkish folk dances and geography distribution in Turkey - Arslan, M. (Journal of Oriental Studies, 2016)
Turkish culture, as yet it is called Anatolian Turks Culture (Turkish Anadolu Kültürü) is a legacy of the millennial culture clusters of different nations. Turkish folk dances – the result of the interpenetration of different cultures and traditions for thousands of years. From the standpoint of diversity Folk Dance Turkey is the richest country in the world. The number of folk dances in Turkey is so great that there are still not all of them collected and systematized. In Turkey, there are about 4000. Turkish folk dance is an important element of Turkish folklore. All folk dances have a story and theme. Almost all regions, towns and villages there are different folk dances, costumes and music.